Penerapan Metode SMART dalam Seleksi Penerima Bantuan Sosial Warga Masyarakat Terdampak COVID-19 - Bambang TJ Hutagalung; Elida Tuti Siregar; Juanda Hakim Lubis (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The Tabita Women's Association (PW) faces obstacles in determining objective criteria in determining community members affected by Covid-19 for social assistance to be distributed so that they are right on target. This is due to the absence of a systematic and measurable system in determining which citizens are eligible as recipients of social assistance. To help PW Tabita, it is necessary to establish a system capable of providing output recommendations for the selection of the most appropriate community members as recipients of social assistance. The criteria for selecting social assistance recipients refer to the fulfillment of several elements, namely: employment status, monthly income, number of dependents, residence status, electricity tariff status, insurance participants, and PKH (Family Hope Program) participants. The Simple Multi-Attribute Rating Technique (SMART) method is a method applied in this research. The results showed that determining the appropriate weight for each criterion greatly influenced the results of the calculation of the recommendation for providing social funds for people affected by Covid-19. Then in order to obtain more accurate results, it is necessary to test the validity of the criteria to obtain more precise criteria in accordance with the eligibility needs of receiving social funds for community members affected by Covid-19 from PW Tabita.